A Rapid, Highly Sensitive and Selective Phosgene Sensor Based on 5, 6‐Pinenepyridine. Issue 55 (1st August 2022) - Solea, Atena B.; Curty, Christophe; Fromm, Katharina M.; Allemann, Christophe; Mamula Steiner, Olimpia
Abstract: The toxicity of phosgene (COCl2 ) combined with its extensive use as a reactant and building block in the chemical industry make its fast and accurate detection a prerequisite. We have developed a carboxylic derivative of 5, 6‐pinenepyridine which is able to act as colorimetric and fluorimetric sensor for phosgene in air and solution. For the first time, the formation of a pyrido‐[2, 1‐ a ]isoindolone was used for this purpose. In solution, the sensing reaction is extremely fast (under 5 s), selective and highly sensitive, with a limit of detection (LOD) of 9.7 nM/0.8 ppb. When fixed on a solid support, the sensor is able to detect the presence of gaseous phosgene down to concentrations of 0.1 ppm, one of the lowest values reported to date. Abstract : A phosgene sensor based on 5, 6‐pinenepyridine was developed. This sensor shows remarkable selectivity and sensitivity down to 9.7 nM/0.8 ppb in solution, with a response time of under 5 seconds. When fixed on a solid support, gaseous phosgene is detected down to concentrations of 0.1 ppm.